Registration Of Name Rights To Land Object Auction (Study in Mataram City) - Arief Rahman; Wiwiek Wahyuningsih; Shinta Andriyani (Unram Law Review, 2022)
This study examines the procedure for transferring the title to the auction object. The type of research used in this article is normative and empirical research using the statutory approach, conceptual approach, and practical approach. The results showed that the implementation of the transfer of name procedures for the transfer of land rights through auction, namely: 1) Applying for registration of the transfer of ownership rights to land due to auction through the service counter that has been provided, 2) The Land Office Service Counter Officer conducts Examination of Application Files, 3 ) Paying Land Rights Registration Fee, 4) Carrying out the Work Process, Recording and Correspondence, 5) Issuing certificates, 6) Submission of certificates. Meanwhile, if there are objections raised by the owner of the land being auctioned (debtors in default), related to the application for land registration submitted by the winner of the auction (buyer), then in this case the National Land Agency will temporarily suspend the application process for the transfer of the name of the auction object until there is a settlement, between the disputing parties.